MORAL JUDGMENT OF ILLOCUTIONARY ACT IN THE 10TH EPISODE OF VIOLET EVERGARDEN ANIME - Sri Endah Tabiati; Ryan Hilman Aziz (IKIP Siliwangi, 2023)
This study explores the linkage between illocutionary acts and moral judgments from researchers’ and respondents’ perspectives by using the 10th episode of Violet Evergarden’s anime. By using mixed methods, the authors collected the data using note-taking methods and analysed the utterances from their perspectives and the moral story based on their and participants’ views. Next, the authors distributed a pre-online questionnaire, including a website link to watch the anime. After filling in the demography data and watching the anime, the participants answered a post-online questionnaire about this episode in moral judgment contexts. This study found that the assertive type is the significant utterance containing 77 (51%) utterances and 151 illocutionary acts utterances, including the central characters of the anime (Ann: 38/67); (Violet: 24/40). Moreover, the third character showed the directive-type of illocutionary act dominantly (Clara: 17/44). Furthermore, in line with the author’s finding, both perspectives found the matching result of moral judgments (connectedness: 85%); (sadness: 85%); (love tension: 90%); and (tension: 85%). Thus, the significantly contained utterances in this episode are reciprocal with its moral judgment from both views. Keywords: Illocutionary Acts; Moral Judgment; Anime